Nanostructured Lipid Carriers in Chemotherapeutics: An Overview - Sabale, Vidya; Jiwankar, Manasi (Indian Journal of Pharmaceutical Education and Research, 2023)
Cancer is a life-threatening disease that is associated with persistent tissue injury and uncontrolled cell growth. The treatments available to treat cancer are chemotherapy, surgery and radiation therapy. These treatments are used in combinations, while the most preferred treatment is chemotherapy. Because of the Non-specificity of anticancer drugs, they kill normal healthy cells along with cancer cells which lead to severe side effects. To minimize such limitations associated with conventional chemotherapy, nanostructured lipids carriers can be developed. These are nanocarriers consisting of a mixture of solid and liquid lipids along with surfactants. Lipids used in the formulation of NLCs are biocompatible and biodegradable. NLCs ensure high drug payload, less drug expulsion and more stability on storage. NLCs enhance the aqueous solubility of lipophilic anticancer drugs. Their surface modification can help to overcome drug resistance in cancer therapy. Controlled and targeted drug delivery of anticancer drugs can be possible by formulating them as NLCs. NLCs can play an important role in targeting anticancer drugs by different mechanisms. This review highlights types, formulation methods, characterization of nanostructured lipid carriers and strategies to achieve targeted release of anticancer drugs loaded in NLCs.
Keywords: Cancer; Nanostructured lipid carriers; Drug targeting; Lipids; Anticancer drugs